(untitled) (Anclajes, 2016)
In El Torito de los Muchachos (1830), Luis Pérez deploys voices, not always Gauchos and Federalists, but sometimes Uniterian and literate, who utter fictional truths in the form of a confession. In a historical moment in which the press was a vehicle of influence on public opinion, Pérez aims his publications toward broad swaths of the public to include of illiterate groups through oral readings. This paper analyzes the ways in which these confessions allowed truths to stand up amid a war of words, as they sought to occupy an imagined public space on whose field discursive conflicts were fought.